Eksplorasi Ontologis & Epistemologis 'Logos' dalam Yohanes 1:1 melalui Perspektif Filsafat Metafisik - Daniel Pesah Purwonugroho (Sekolah Tinggi Teologi Kalvary - Maluku Utara, 2025)
This paper explores the concept of logos in John 1:1 ontologically and epistemologically through the perspective of metaphysical philosophy. The concept of logos metaphysically generally emphasizes a principle that governs the cosmos. Logos from an ontological perspective is the fundamental thing that supports human existence. Logos epistemologically is a framework that expresses knowledge. Logos in John 1:1 has a meaning and concept that goes beyond that. John synthesizes logos to emphasize Jesus Christ, not just an abstract concept. John's synthesis of logos brings the concept and meaning of logos to be evolved. Through a descriptive qualitative approach, the author tries to explore the ontological and epistemological logos through the perspective of metaphysical philosophy and see it in John 1:1. Metaphysical philosophy's exploration of the ontological and epistemological logos enriches the meaning of logos in John 1:1, but John evaluates the exploration in the person of Jesus Christ.